The Moderating Effect of Social Support on Parental Stress and Depression in Mothers of Children with Disabilities - Gyeong-A Park; Oan Na Lee (Occupational Therapy International)
Purpose. Mothers caring for children with disabilities often experience parental stress, which may lead them to suffer from depression. It is necessary to find a way to relieve their stress and depression. Therefore, we examined the effect of parental stress on depression and the buffering role of social support between them in a sample of 164 mothers of children with disabilities. Participants. One hundred and sixty-four participants (aged 25–58 years) in Gwangju and Jeollanamdo, South Korea, completed a set of self-reported measures. Methods. Parental stress, depression, and social support are assessed by Parental Stress Index, Multidimensional Scale Perceived Social Support, and Center for Epidemiological Studies Depression Scale, respectively. Results. Parental stress significantly predicted depression, and social support showed the buffering effect on the relationship between parental stress and depression among mothers of children with disabilities. These findings indicate that mothers who perceive a high level of social support are less likely to experience depression. Conclusions. This study shows the moderating effect of social support on the relationship between parental stress and depression among mothers of children with disabilities. The level of depression they experience is not that great if they perceive a high level of social support even if they experience a high level of parental stress. These findings imply that social support is a critical resource that prevents the negative effect of parental stress on depression among mothers of children with disabilities.